Endoscopic-Assisted Lateral Corridor to the Infratemporal Fossa: Proposal and Quantitative Comparison to the Endoscopic Transpterygoid Approach - Yacoub, Abraam; Schneider, Daniel; Ali, Ahmed; Wimmer, Wilhelm; Caversaccio, Marco; Anschuetz, Lukas (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective This study was aimed to propose an expanded endoscopic-assisted lateral approach to the infratemporal fossa (ITF) and compare its area of exposure and surgical freedom with the endoscopic endonasal transptergyoid approach (EETA).Methods Anatomical dissections were performed in five cadaver heads (10 sides). The ITF was first examined through the endoscopically assisted lateral corridor, herein referred to as the endoscopic-assisted transtemporal fossa approach (TTFA). After that, the EETA was performed and coupled with two sequential maxillary procedures (medial maxillectomy [MM], and endoscopic-assisted Denker's approach [DA]). Using the stereotactic neuronavigation, measurements of the area of exposure and surgical freedom at the foramen ovale were determined for the previously mentioned approaches.Results Bimanual exploration of the ITF through the endoscopic-assisted lateral approach was achieved in all specimens. The DA (729 ± 49 mm2) provided a larger area of exposure than MM (568 ± 46 mm2; p < 0.0001). However, areas of exposure were similar between the DA and the TTFA (677 ± 35 mm2; p = 0.09). The surgical freedom offered by the TTFA (109.3 ± 19 cm2) was much greater than the DA (24.7 ± 4.8 cm2; p < 0.0001), and the MM (15.2 ± 3.2 cm2, p < 0.0001).Conclusion The study demonstrates the feasibility of the proposed approach to provide direct access to the extreme extensions of the ITF. The lateral corridor offers an ideal working area in the posterior compartment of the ITF without crossing over important neurovascular structures. The new technique may be used alone in selected primary ITF lesions or in combination with endonasal approaches in pathologies spreading laterally from the nose or nasopharynx.
Keywords: Infratemporal fossa; endoscopic transpterygoid approach; endoscopic-assisted Denker's approach; medial maxillectomy; cranial base surgery